Stress in music teaching: identifying the level and source of stress in the context of Malaysian primary schools. - Chan, Cheong Jan; Jamaludin, Juriani (Universiti Putra Malaysia Press, 2010)
This study was designed to examine the level of stress according to selected stressors experienced by primary school music teachers. The stressors undertaken in this study were categorized into six sub-scales which are ‘student characteristics’, ‘teacher characteristics’, administrative procedures’, ‘social support’, ‘facilities and equipment’ and ‘music syllabus contents’. Respondents for this study consisted of 326 trained and untrained music teachers in Selangor. Music Teacher Stress Inventory was developed based on problems faced by Malaysian music teachers, with 44 stressors extracted from 99 sources of stress, collected from various sources. Findings of the present research indicate that music teachers in this study were generally experiencing mild stress in teaching music. Among particular item of stressors, ‘lack of trained music teacher’, ‘lack of music resources and books’, ‘lack of skill in playing musical instrument’, ‘inadequate allocation to buy costumes for music performance’ and ‘lack of recognition for music education’ were rated by the teachers as the main sources of their stress.